ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS LAYANAN OJEK ONLINE (WAKJEK) DI KOTA BATAM - Yovan Sawir Saputra; Shinta Wahyu Hati (Politeknik Negeri Batam, 2017)
This study aims to measure the level of customer satisfaction with the quality of their online service (Wakjek) in Batam city. Primary data obtained by spreading the questionnaires to consumers using Random Sampling techniques with the total sample as many as 100 respondents. The data were analyzed using descriptive statistics. Consumer satisfaction against the dimensions of quality is described in the diagram of the Importance-Performance Analysis (IPA). IPA charts indicate that service dimension items scattered on the four quadrants, namely 15 items on A quadrant which is a top priority, 7 items in quadrant B that should be preserved, the next 7 items in quadrant C which is a low priority, as well as 12 items in quadrant D is an item that is considered less important. Research results exposed that the satisfaction of services provided by taxi online Wakjek has shown the good results it can be seen from the level of conformity that is indicated by the variable Y i.e. satisfaction service. On the attributes of the performance of the average value of the variable Y indicates the number of attributes exists while 4.77 hopes the average value of the variable Y shows numbers 3.62. This means that service satisfaction felt by customers of their online Wakjek have been able to meet the expectations of their customers online Wakjek itself but there are still some items that must be repaired